Factor analysis of sarcoidosis phenotypes at two referral centers in Brazil - Rodrigues, S.C.S.; Rocha, N.A.S.; Lima, et al., M.S. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2011)
Background: In sarcoidosis, clinical presentations and outcomes vary widely. Objective: To characterize the clinical phenotypes of sarcoidosis, by factor analysis, in a series of cases with long-term follow-up.Methods: We conducted a retrospective study involving 137 patients with biopsy-confirmed sarcoidosis, recruited from two referral centers in Sao Paulo, Brazil. Organ involvement was evaluated in accordance with a previously established protocol. Sarcoidosis phenotypes were characterized by factor analysis. Results: Follow-up ranged from 6 to 144 months. Four factors (phenotypes) were identified: relevant residual pulmonary fibrosis; relapse; residual airflow limitation; and acute disease. The four factors collectively accounted for 66% of the total variance. Patients with relevant residual pulmonary fibrosis were older and presented with the following: greater symptom duration; skin involvement; low forced vital capacity; low forced expiratory volume in one second/forced vital capacity ratio; and more advanced radiographic stages at baseline. The relapse phenotype was associated with chronic disease, greater dyspnea severity, neurologic involvement, and cardiac involvement. Patients with residual airflow limitation more often had airflow obstruction at baseline, chronic disease, and relevant residual pulmonary fibrosis. Acute disease was associated with being younger, weight loss, scoring lower for dyspnea, and having extensive involvement. Abnormal calcium metabolism was associated with acute disease and with relapse. Conclusions: Sarcoidosis can be categorized into four different clinical phenotypes: three that are chronic; and one that is acute and self-limiting. In many cases, these phenotypes can be easily recognized.